BENCHMARKING - Eduardus Tandelilin (Journal of Indonesian Economy and Business (JIEB), 1997)
This article aims to develop an integral summary of the present status of the model ("philosophy") of benchmarking. It includes the presentation of different bencmarking definitions, different benchmarking processes, preconditions for benchmarkig, and finally, to propose an alternative benchmarking model, processes of how to accomplish continuous improvement would be performed.